Sex Differences in the Presentation, Diagnosis, and Management of Acute Coronary Syndromes: Findings From the Kerala-India ACS Registry - Patel, Amisha (Glob Heart, 2015)
BACKGROUND: Previous literature from high-income countries has repeatedly shown sex differences in the presentation, diagnosis, and management of acute coronary syndromes (ACS), with women having atypical presentations and undergoing less aggressive diagnostic and therapeutic measures. However, much less data exist evaluating sex differences in ACS in India. OBJECTIVES: This study sought to evaluate sex differences in the diagnosis, management, and treatment of patients with ACS in Kerala, India. METHODS: The Kerala ACS Registry collected data from 25,748 consecutive ACS admissions (19,923 men and 5,825 women) from 125 hospitals in the Indian state of Kerala from 2007 to 2009. This study evaluated the association between sex differences in presentation, in-hospital management, and discharge care with in-hospital mortality and in-hospital major adverse cardiovascular events (defined as death, reinfarction, stroke, heart failure, or cardiogenic shock). RESULTS: Women with ACS were older than men with ACS (64 vs. 59, p < 0.001) and were more likely to have a history of previous myocardial infarction (16% vs. 14%, p < 0.001). Inpatient diagnostics and management and discharge care were similar between sexes. No significant differences between men and women in the outcome of death (odds ratio [OR]: 1.05, 95% confidence interval [CI]: 0.80 to 1.38) or in the composite outcome of death, reinfarction, stroke, heart failure, or cardiogenic shock (OR: 0.99, 95% CI: 0.79 to 1.25) were seen after adjustment for possible confounding factors. CONCLUSIONS: In Kerala, even though women with ACS were older and more likely to have previous myocardial infarction, there were no significant differences in in-hospital and discharge management, in-hospital mortality, or major adverse cardiovascular events between sexes. Whether these results apply to other parts of India or acute presentations of other chronic diseases in low- and middle-income countries warrants further study.